Proceso de atención de enfermería en paciente de sexo masculino de 1 año 5 meses de edad con adenomegalia. - Escobar Oleas, Evelyn Rosa (2020)
A 1 year 5 month old male pediatric patient is taken by his parents to a hospital unit presenting a fever of 39oC, irritability, swelling in the neck, lack of appetite, mother refers that he has been suffering from these symptoms for 3 days, but the reason for this is because of the hyperthermia he presents and the discomfort. Adenopathies are one of the most frequent reasons for consulting a pediatric hematologist. Although most cases correspond to self-limited transitory benign processes, on some occasions they may be initial manifestations of more serious pathologies, mainly related to malignant diseases. (Genes, 2018). It was achieved to apply the process of nursing care in the pediatric patient of 1 year 5 months who presents adenomegaly not specified in such a way that satisfactory results were obtained, where the nurse plays the role of providing care based on theories to put them into practice and thus be able to observe the recovery in the patient, where all the proposed objectives were met.